2005
DOI: 10.1017/s1355617705050861
|View full text |Cite
|
Sign up to set email alerts
|

Implicit learning of non-spatial sequences in schizophrenia

Abstract: Recent studies have reported abnormal implicit learning of sequential patterns in patients with schizophrenia. Because these studies were based on visuospatial cues, the question remained whether patients were impaired simply due to the demands of spatial processing. This study examined implicit sequence learning in 24 patients with schizophrenia and 24 healthy controls using a non-spatial variation of the serial reaction time test (SRT) in which pattern stimuli alternated with random stimuli on every other tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 35 publications
4
20
0
Order By: Relevance
“…These results are consistent with studies finding no deficit in implicit learning in schizophrenia (Kéri et al, 2000;Danion et al, 2001;Marvel et al, 2005; for review see: Gold et al, 2009). In contrast with studies that assay explicit statistical learning and inference using more cognitive tasks (i.e.…”
Section: Acquisition Of Visual Prior Expectationssupporting
confidence: 88%
“…These results are consistent with studies finding no deficit in implicit learning in schizophrenia (Kéri et al, 2000;Danion et al, 2001;Marvel et al, 2005; for review see: Gold et al, 2009). In contrast with studies that assay explicit statistical learning and inference using more cognitive tasks (i.e.…”
Section: Acquisition Of Visual Prior Expectationssupporting
confidence: 88%
“…However, an inability to become sensitive to the abstract quality of the spatial relations may explain why these high-generation patients failed to show a continued increase in trial type differences across blocks, as controls did. Using a similar probabilistic sequence learning paradigm, Marvel et al (2005) also found that trial type differences in the schizophrenia group leveled off early in testing and did not change across sessions. Taken together, these studies indicate that patients may have a limit, not on how quickly they learn sequential regularities but rather on the level of sensitivity they develop with extended exposure (i.e., their asymptote).…”
Section: Discussionmentioning
confidence: 85%
“…Since response time becomes slower and more variable with age, the time between successive event onsets is longer and more variable for old than young people. The focus of the present study is healthy aging, but similar arguments apply to other populations that show impaired sequence learning such as Parkinson's and Huntington's disease patients (Helmuth et al, 2000;Willingham et al, 1996), early dementia patients (Negash et al, 2006), schizophrenics (Marvel et al, 2005) and dyslexics (J. H. Howard, Jr, et al, 2006;Vicari et al, 2005).…”
Section: Introductionmentioning
confidence: 68%